Occupational safety and health risks in dock work: a narrative literature review - Barbieri, Anna; Sabatini, Laura; Graziosi, Francesca; Severi, Elena; Mancini, Gianpiero; Violante, Francesco Saverio (La Medicina del Lavoro, 2014)
Background: Seaports are complex systems where workers can be exposed to a large variety of safety and health risks. Nevertheless, the literature available on this topic is scarce, if we exclude the specific area of the shipbuilding industry. Objectives and methods: The aim of this paper is to provide a review of the scientific evidence concerning the occupational risks in seaports. Literature on this theme, obtained consulting the main databases (PubMed, Scholar and CCOHS) up to 2012, was reviewed. Results: Loading/unloading procedures, transport and storage of goods in docks are identified as the major causes of injuries (such as falls, crushing and entrapments) and accidents (release of chemicals, fires or explosions). Moreover, attention is drawn to the risks related to goods handled: in particular, authors described risks of asphyxia or intoxication in restricted and poorly ventilated areas such as containers or ship holds. Conclusions: The following main prevention measures were identified by all authors as those most effective: implementation of workers’ training and information and intensification of controls on ships, particularly concerning loading/unloading procedures and documents accompanying the goods.